Status Nutrisi Pasien Hemodialisa di Rumah Sakit Umum Daerah - Yusnaini Siagian (Jurnal Keperawatan Silampari, 2018)
The purpose of this study was to determine the nutritional intake of hemodialysis patients at the Regional General Hospital of DR. Pirngadi Medan. This research is a quantitative study using descriptive methods. The results of this study found the characteristics of the majority of respondents aged 45-54 years as many as 37 people (40.2%), male sex that is 48 people (52.2%), the highest education level was 42 people (45.7%) ) and no longer work as many as 73 people (79.3%). The majority of respondents with married status are 70 people (76.1%), the majority of respondents have undergone hemodialysis> 3 years which is 48 people (52.2%) and the majority of illnesses that cause respondents to undergo hemodialysis are hypertension namely 52 people (56.5%) . The nutritional intake of respondents more or less than good nutritional intake of 64 people (69.6%). Conclusions, hemodialysis patients at the Regional General Hospital Dr. Pirngadi Medan experiences nutritional status disturbances, making them at risk of complications due to nutritional deficiencies that can reduce their quality of life. Keywords: Hemodialysis, Patients, Nutrition Status